2020
DOI: 10.4236/ce.2020.1110138
|View full text |Cite
|
Sign up to set email alerts
|

Developing Pre-Service Teachers’ Mathematics TPACK through an Integrated Pedagogical Course

Abstract: Lesson planning and presentation are regarded as an effective method that allows pre-service teachers to gain experience in the instructional processes and improve teaching skills. Lesson Portfolio and Presentations, not only is utilized as a method for increasing the quality of a teacher's education, but also used to research the Technological Pedagogical Content Knowledge (TPACK) framework. The purpose was to investigate changes in pre-service teachers' TPACK from their lesson portfolio and presentation prac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
3
1
0
Order By: Relevance
“…The main conclusion of the current study, thus, taking into consideration the effectiveness of the training program TIMSS-based shown by this study, the recommendation is that math teachers, in general, participate in effective training programs and teaching strategies. This is consistent with the recommendations of many previous studies that indicated the effectiveness of using training programs and teaching strategies in developing mathematical reasoning and its sub-skills, such as the study of Abdallah and Wardat (2021), Assadi and Hibi (2020), Berisha and Vula (2021), Burroughs and Luebeck (2010), Higgins et al (2016), andLivy et al (2016); so, it is necessary to note to the planners of the math curriculum the importance of focusing on developing mathematical reasoning and sub-skills among pre-service and in-service math teachers, by subjecting them to training programs, training courses, and workshops to train them on how to use appropriate teaching strategies and programs, especially those based on international studies such as TIMSS or PISA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The main conclusion of the current study, thus, taking into consideration the effectiveness of the training program TIMSS-based shown by this study, the recommendation is that math teachers, in general, participate in effective training programs and teaching strategies. This is consistent with the recommendations of many previous studies that indicated the effectiveness of using training programs and teaching strategies in developing mathematical reasoning and its sub-skills, such as the study of Abdallah and Wardat (2021), Assadi and Hibi (2020), Berisha and Vula (2021), Burroughs and Luebeck (2010), Higgins et al (2016), andLivy et al (2016); so, it is necessary to note to the planners of the math curriculum the importance of focusing on developing mathematical reasoning and sub-skills among pre-service and in-service math teachers, by subjecting them to training programs, training courses, and workshops to train them on how to use appropriate teaching strategies and programs, especially those based on international studies such as TIMSS or PISA.…”
Section: Discussionsupporting
confidence: 91%
“…By reviewing the theoretical and research literature, as well as looking at some scales of habits of mind in math (Assadi & Hibi, 2020;Berisha & Vula, 2021;Fannakhosrow et al, 2022;Tinh et al, 2021;), a standing scale was prepared at the form of a questionnaire according to the 5-choice Likert scale, that consisted of 30 items that included three sub-scales (thinking flexibly, metacognition, and questioning & posing problems), with a maximum score of 150 and a minimum score of 30.…”
Section: The Habits Of Mind Scalementioning
confidence: 99%
“…However, the results of this study also imply the need for an integrated approach, in line with research by Marbán & Sintema [23], Hill & Uribe-Florez [24], and Assadi & Hibi [25], who highlighted the importance of integrating TPACK in mathematics education curricula. Along with Dong & Chen [26] and Tabah & Trgalová [27] findings indicating special attention to understanding mathematics content, these results underscore the complexity of developing TPACK competencies among mathematics education students.…”
Section: Discussion Of the Resultssupporting
confidence: 86%
“…This conclusion aligns with the findings of Mavani (2020), who extensively examined the concept of autonomy and its relationship to the successful integration of the software. The findings presented in this segment are in line with the findings of Assadi & Hibi (2020).…”
Section: Attitudes Towards Mathematics Teachingsupporting
confidence: 90%